The Effect of Age on Right Ventricular Systolic Function Using Traditional Echocardiographic Measures - Elham Hussien Manhal Al-Obaidi; Asaad Hasan Noaman Al-Aboodi (مجلة الكوفة الطبية)
Background: In a wide range of clinical settings, comprehensive evaluation of the right ventricle has become increasingly essential. Measures of right ventricle systolic function, including fractional area change, tissue Doppler, S velocity, tricuspid annular plane systolic excursion, show a significant variation in previous studies and different data known regarding how these measurements change with age. Aim of the study: The aim of this study is to evaluate the effects of age on right ventricle systolic function by using conventional 2D echocardiographic assessment. Patients and methods: Comprehensive transthoracic echocardiography examinations were performed on 103 healthy adult volunteers, mean age 37.1±11.9 years (range: 20-66), to determine age related changes in right ventricle dimensions and function. Results: The assessment of right ventricle function demonstrates slightly significant differences in tricuspid annular plane systolic excursion (r= -.197, p = .047), and FAC (r= -.241, p = .015), among age groups, with a non-significant very small negative relationship between age and tissue Dopplers (r= -.0925, p = .355). Conclusions: This study has demonstrated that age-adjusted measures are required for the evaluation of right ventricle function. Further, the conventional techniques may ignore mild or slight changes leading to underestimated assessment which regarded as a fundamental challenge for their use; so, the use of advanced techniques which allow early identification of right ventricle dysfunction are recommended since they can detect subclinical dysfunction before anomalies revealed by traditional echocardiography occur.